Posterior maxillary ostectomy for mandibular implant insertion. - (:unkn) unknown (My University, 1995)
Posterior maxillary ostectomy was performed for a patient who had extruded left maxillary molars into the edentulous mandibular region. With this procedure, enough interarch space was obtained, and one screw implant was simultaneously inserted in the edentulous mandibular posterior ridge.